Parameterised finite element model for S&C Benchmark in Matlab and Abaqus format - Pålsson, Björn (Chalmers University of Technology, 2021)
A finite element model of a 60E1-R760-1:15 turnout with parameterised rail pad and ballast properties for simulation Benchmark purposes.

The matlab script WriteAbaqus_210927 generates a turnout FE model in Abaqus format with the track stiffness properties (ballast and pad) and nodal constraints defined at the top of the file.

An overview of the model is provided in the article

Björn A. Pålsson, Ramakrishnan Ambur, Michel Sebès, Ping Wang, Jou-Yi Shih,
Demeng Fan, Jingmang Xu, and Jiayin Chen, A comparison of track model formulations for simulation of dynamic
vehicle–track interaction in switches and crossings, Vehicle System Dynamics, https://doi.org/10.1080/00423114.2021.1983183

The main file for the FE model is called TurnoutMaster.inp An optional tangent track extension section of 25.2 metres can be written if trackExtensionFlag=1. The main file is called TrackExtensionMaster.inp

The rail and sleeper body files are provided "as is" while the bushing properties and nodal constraint files are updated each time the script is run.

The rail and sleeper bodies are available in the zip folder RailAndSleeperBodies.zip

Example models for the calulation of track receptance are included in the folders Turnout_1 and TrackExtension_1.

The Turnout_1 model also includes a file called RUNNING_SURFACE_NODES.inp with sets of nodes for the different rails required for some software implementations (e.g. Simpack linear flextrack) and for simulations of traffic in the through and diverging routes.

If the track extension is used, additional node sets would have to be created for those rails as well, but it's straightforward to use the nodes of the straight rail bodies for this purpose.

En finita element-modell av en 60E1-R760-1:15 spårväxel med parameteriserade egenskaper för rälbefästningar och ballastegenskaper.

En beskrivning av innehållet i datasetet finns på den engelska katalogsidan.
Parameteriserad finita element-modell för S&C Benchmark i Matlab och Abaqus-format
Keywords: RAILWAY TRANSPORT; JÄRNVÄGSTRANSPORT; Finite Element Analysis; Finita element-metoden; turnout; spårväxel; Applied Mechanics; Teknisk mekanik; Transportation; Transporter